EUTECTIC IONIC LIQUID MEDIATED ELECTROCHEMICAL SYSTEM FOR DYES EXTRACTION OR DEGRADATION - ABDUL RASHID, MUHAMMAD ISKANDAR (IRC, 2019)
Textile wastewater is notoriously known to contain strong colour, a highly fluctuating pH and significant Chemical Oxygen Demand (COD) values. Because of these characteristics, treatment of these effluent has been rather difficult. Traditional methods for dealing with textile wastewater consist of various combinations of biological, physical and chemical methods. Traditional methods usually use ionic liquid and it will pollute the wastewater as it produces toxic solution. Eutectic Ionic liquid is one of the alternatives to replace metallic ionic liquid because it is recyclable and green economically. For this project, it will be using eutectic ionic liquid as electrolyte to extract dyes from wastewater from industry. It will undergo oxidation to produce water and carbon dioxide. By using eutectic ionic liquid, no metallic or toxic will produce and it will not pollute the river. By doing this, the wastewater can be removed to the river by minimising the pollution of water. This project will study about the concentration of the dyes after being treat using electrolysis mediated deep eutectic solvent.